PEER-ASSESSMENT THROUGH PADLET TO EVALUATE STUDENTS’ WRITING SKILL - Aisyah, Aisyah; Lustiyantie, Ninuk; Murtadho, Fathiaty (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2024)
Peer-assessment is an effective way to improve the quality of student learning. The aim of this research is to find students' perceptions of using Padlet in peer assessment in writing English language learning process. This research uses a qualitative descriptive method with data collection techniques using questionnaires. The questionnaire used contained 10 questions to gather information regarding the perception of students regarding the use of Padlet. It is hoped that the results of this study will provide benefits in various aspects, namely, (1) theoretical benefits, this study is expected to provide a deeper understanding of the application of peer assessment with technology to learning, (2) practical benefits, and (3) for the learning process of both students and teachers. Based on the research results, it can be concluded that English is one of the most important skills for students to learn because it will greatly influence students' skills in acquiring new knowledge.